Cornerstones. - Baker, George; Bal, Mieke; Blom, Ina; Crimp, Douglas; Friedel, Helmut; Kuspit, Donald; Lütticken, Sven; Osborne, Peter; Pontbriand, Chantal; Silverman, Kaja; Van den Boogerd, Dominic; Wagner, Anne, M.; et al. ([s.l.] : Sternberg Press, 2011)
Acconci Vito ; Bourgeois Louise ; Byrne, Gerard ; Daniëls, René ; Kelley, Mike ; Matta-Clark, Gordon ; Picasso, Pablo ; Rainer, Yvonne ; Richter, Gerard ; Salcedo, Doris et al.
This publication appeared following a monthly lecture series of the same name, held at Witte de With Center for Contemporary Art between February 7, 2008 and May 28, 2009.
boek